The Hotel Nantucket : a novel - Hilderbrand, Elin (Little, Brown and Company, 2022)
"The queen of beach reads" (New York Magazine) delivers another immensely satisfying page-turner in this tale about a summer of scandal at a storied Nantucket hotel.